2011
DOI: 10.1016/j.imbio.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocyte proliferation is suppressed by the opioid growth factor–opioid growth factor receptor axis: Implication for the treatment of autoimmune diseases

Abstract: Endogenous opioids are known to repress the incidence and progression of autoimmune diseases. One native opioid peptide, [Met⁵]-enkephalin, termed the opioid gowth factor (OGF), interacts with the OGF receptor (OGFr) to suppress the expression of experimental autoimmune encephalomyelitis. The present study examined the role of the OGF-OGFr axis in the regulation of B lymphocyte proliferation. Murine B lymphocytes were stimulated with lipopolysaccharide. Both OGF and OGFr were present in all B lymphocytes. OGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 59 publications
3
36
0
Order By: Relevance
“…CD and other autoimmune diseases are widely thought to be related to T-cell-mediated immunity, although there is evidence for humoral immunity in the disease process by an antigen-driven B-cell response. T and B cells depend on proliferation for response and OGF depresses T-and B-cell proliferation by an OGFr-dependent inhibitory pathway involving p16 and p21 [21,22]. As added evidence that opioid antagonists do not have a direct effect on immune response, continuous opioid receptor blockade by NTX has no effect on T-or B-cell proliferation.…”
Section: Editorialmentioning
confidence: 98%
See 1 more Smart Citation
“…CD and other autoimmune diseases are widely thought to be related to T-cell-mediated immunity, although there is evidence for humoral immunity in the disease process by an antigen-driven B-cell response. T and B cells depend on proliferation for response and OGF depresses T-and B-cell proliferation by an OGFr-dependent inhibitory pathway involving p16 and p21 [21,22]. As added evidence that opioid antagonists do not have a direct effect on immune response, continuous opioid receptor blockade by NTX has no effect on T-or B-cell proliferation.…”
Section: Editorialmentioning
confidence: 98%
“…This may be due in large part because only small amounts of preproenkephalin-derived peptides, which require dibasic cleavage for formation of smaller peptides (e.g., OGF) and are the opioid-active forms, have been recorded in T lymphocytes. However, the OGFr has been documented in T and B cells, and this peptide is fully capable of inhibiting cell proliferation through p16 and p21 cyclin-dependent inhibitory kinase pathways [21,22].…”
Section: Editorialmentioning
confidence: 99%
“…Specificity of T-cell populations that were inhibited by PEA was not defined in this study as the CD3 antibody stains multiple T lymphocytes. However, because MOG-induced EAE is a Th 1-mediated model ofdisease, the reduction in T cells would include Th 1 T lymphocytes (25). Analysis of T-cell proliferation in tissues was conducted with an antibody (CD3) and therefore did not distinguish whether PEA was targeting CD4+ or CD8+ cells.…”
Section: Effect Ofpea On Neuropathologymentioning
confidence: 99%
“…1 MENK, composed of Tye-Gly-Gly-Phe-Met, is derived from pre-enkephalin and circulates in blood at low concentration in body. 2 The data from both early documented studies [3][4][5] and published results in our laboratory indicated that MENK at suitable range of concentrations could enhance activity of various types of immune cells, like: augmenting interactions between dendritic cells (DCs) and CD4+T cells, induction of phenotypic and functional maturation of DCs with increased antigen presentation, improvement of antitumor activity of DCs loaded with antigen, induction of macrophage polarization to the M1 phenotype in mouse model, eliciting CD8+T cell cytotoxicity, upregulating the secretion of cytokines such as IL-2, IL-12, IFN-γ, TNF-α, increasing the release of hydrogen peroxide and nitric oxide and stimulation of lymphocyte subpopulations in normal human donors. [6][7][8][9][10][11][12] In addition, there have been studies indicating that MENK could inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%